Investigation of the high-strain rate (shock and ballistic) response of the elastomeric tissue simulant Perma-Gel®. (August 2016) - Appleby-Thomas, G.J.; Wood, D.C.; Hameed, A.; Painter, J.; Le-Seelleur, V.; Fitzmaurice, B.C.
Highlights: Plate-impact and ballistics tests on the epithelial/muscular analogue Perma-Gel ® . Us -up and σx -up /σx -v equations-of-state established for the first time. Perma-Gel's ® high-rate compressibility tentatively linked to ballistic response. Importance of individual tissue analogue material properties highlighted. Importance of composite rather than individual simulants noted. Graphical Abstract: Abstract: For both ethical and practical reasons accurate tissue simulant materials are essential for ballistic testing applications. A wide variety of different materials have been previously adopted for such roles, ranging from gelatin to ballistics soap. However, while often well characterised quasi-statically, there is typically a paucity of information on the high strain-rate response of such materials in the literature. Here, building on previous studies by the authors on other tissue analogues, equation-of-state data for the elastomeric epithelial/muscular simulant material Perma-Gel ® is presented, along with results from a series of ballistic tests designed to illustrate its impact-related behaviour. Comparison of both hydrodynamic and ballistic behaviour to that of comparable epithelial tissues/analogues (Sylgard ® and porcine muscle tissue) has provided an insight into the applicability of both Perma-Gel ® and, more generally, monolithic simulants for ballistic testing purposes. Of particular note was an apparent link between the high strain-rate compressibility (evidenced in the Hugoniot relationship in the Us -up plane) and subsequent ballistic response of these materials. Overall, work conducted in this study highlighted the importance of fully characterising tissue analogues – with particular emphasis on the requirement to understand the behaviour of such analogues under impact as part of a system as well as individually.